2013
DOI: 10.1016/j.gpb.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Proteome-Wide Amino aCid and Elemental Composition (PACE) Analysis of Expression Proteomics Data Provides A Fingerprint of Dominant Metabolic Processes

Abstract: Proteome-wide Amino aCid and Elemental composition (PACE) analysis is a novel and informative way of interrogating the proteome. The PACE approach consists of in silico decomposition of proteins detected and quantified in a proteomics experiment into 20 amino acids and five elements (C, H, N, O and S), with protein abundances converted to relative abundances of amino acids and elements. The method is robust and very sensitive; it provides statistically reliable differentiation between very similar proteomes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Relative abundances of amino acid residues among peptide and protein identifications are believed to be known and definitive values. [22] Figure S1, Supporting Information shows the calculated relative frequencies for amino acid residues present in the identified proteins ( Figure S1A, Supporting Information) and peptides ( Figure S1B, Supporting Information) for the colon cancer data set. To calculate amino acid residues frequencies for proteins, we artificially cleaved proteins by trypsin rule with no missed cleavage sites.…”
Section: Resultsmentioning
confidence: 99%
“…Relative abundances of amino acid residues among peptide and protein identifications are believed to be known and definitive values. [22] Figure S1, Supporting Information shows the calculated relative frequencies for amino acid residues present in the identified proteins ( Figure S1A, Supporting Information) and peptides ( Figure S1B, Supporting Information) for the colon cancer data set. To calculate amino acid residues frequencies for proteins, we artificially cleaved proteins by trypsin rule with no missed cleavage sites.…”
Section: Resultsmentioning
confidence: 99%
“…The numbers as showed in the header column represent the sequential numbers of the list of entries in the human complete proteome in FAST format, and the titles of columns in the header row use NO, Ala, Cys, Asp, Glu, Phe, Gly, His, Ile, Lys, Leu, Met, Asn, Pro, Gln, Arg, Ser, Thr, Val, Lysine-rich proteins have nutritive and commercial value to establish transgenic lines of cereals with high lysine content of grains [20]. It was reported that down-regulation of cysteine-rich proteins and down-regulation of methionine-rich proteins can be respectively adopted by Escherichia coli and Synechocystis to sulfur deprivation [15] . Encoded by short open reading frames (sORF), small proteins take part in the developmental processes of plant and animal [21,22] .…”
Section: Resultsmentioning
confidence: 99%
“…The values of these features can be extracted simplely from a linear amino acid sequence. AAC and AAC-derived physicochemical features are powerful features that can predict protein-protein interactions, structural and functional classes of proteins and subcellular locations [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%